Hubungan Kata dan Makna dalam Bahasa Indonesia dan Bahasa Arab: Kajian Semantik - Alifiansyah, Roby Fathan; Irawan, Bambang; Hasan, Nur (Alsina : Journal of Arabic Studies, 2023)
This study aims to determine the relationship between meaning and words in Arabic and Indonesian and their correlation. This research falls under the category of a literature review. Various books, dictionaries, and scholarly journals were used as data sources. Data was obtained through documentation and analyzed using the Miles and Huberman approach. The study results indicate that this linguistic phenomenon provides deep insights into the interaction between meaning and word forms within different cultural contexts. The findings reveal that the linguistic structure and dynamics of Arabic and Indonesian are influenced by phonotactic and semantic factors and the pressure to communicate efficiently. Furthermore, analyzing loanwords and meaning changes across languages enhances understanding of linguistic adaptation processes and semantic shifts